(2x+3y)dx+(y+2)dy=0

Simple and best practice solution for (2x+3y)dx+(y+2)dy=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+3y)dx+(y+2)dy=0 equation:


Simplifying
(2x + 3y) * dx + (y + 2) * dy = 0

Reorder the terms for easier multiplication:
dx(2x + 3y) + (y + 2) * dy = 0
(2x * dx + 3y * dx) + (y + 2) * dy = 0

Reorder the terms:
(3dxy + 2dx2) + (y + 2) * dy = 0
(3dxy + 2dx2) + (y + 2) * dy = 0

Reorder the terms:
3dxy + 2dx2 + (2 + y) * dy = 0

Reorder the terms for easier multiplication:
3dxy + 2dx2 + dy(2 + y) = 0
3dxy + 2dx2 + (2 * dy + y * dy) = 0
3dxy + 2dx2 + (2dy + dy2) = 0

Solving
3dxy + 2dx2 + 2dy + dy2 = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'd'.
d(3xy + 2x2 + 2y + y2) = 0

Subproblem 1

Set the factor 'd' equal to zero and attempt to solve: Simplifying d = 0 Solving d = 0 Move all terms containing d to the left, all other terms to the right. Simplifying d = 0

Subproblem 2

Set the factor '(3xy + 2x2 + 2y + y2)' equal to zero and attempt to solve: Simplifying 3xy + 2x2 + 2y + y2 = 0 Solving 3xy + 2x2 + 2y + y2 = 0 Move all terms containing d to the left, all other terms to the right. Add '-3xy' to each side of the equation. 3xy + 2x2 + 2y + -3xy + y2 = 0 + -3xy Reorder the terms: 3xy + -3xy + 2x2 + 2y + y2 = 0 + -3xy Combine like terms: 3xy + -3xy = 0 0 + 2x2 + 2y + y2 = 0 + -3xy 2x2 + 2y + y2 = 0 + -3xy Remove the zero: 2x2 + 2y + y2 = -3xy Add '-2x2' to each side of the equation. 2x2 + 2y + -2x2 + y2 = -3xy + -2x2 Reorder the terms: 2x2 + -2x2 + 2y + y2 = -3xy + -2x2 Combine like terms: 2x2 + -2x2 = 0 0 + 2y + y2 = -3xy + -2x2 2y + y2 = -3xy + -2x2 Add '-2y' to each side of the equation. 2y + -2y + y2 = -3xy + -2x2 + -2y Combine like terms: 2y + -2y = 0 0 + y2 = -3xy + -2x2 + -2y y2 = -3xy + -2x2 + -2y Add '-1y2' to each side of the equation. y2 + -1y2 = -3xy + -2x2 + -2y + -1y2 Combine like terms: y2 + -1y2 = 0 0 = -3xy + -2x2 + -2y + -1y2 Simplifying 0 = -3xy + -2x2 + -2y + -1y2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

d = {0}

See similar equations:

| -4s+15=25 | | (4x+2)+(5x-7)+3x=180 | | (2x-1)(5x^2+6x-3)= | | y^3+y=50 | | tanx=1.274 | | 187x=374 | | (2w^2-3w+1)(4w^2-7w-2)= | | 12=x+9-5x | | X+(-11)=13 | | x^2+y^2=1 | | (7x^2-5x-3)(2x+4)= | | X-(-9)=24 | | +2n=+4 | | 1/64 | | ln(3x-15)=5 | | y=x2+2 | | (3v-4)(2v^2+6v+7)= | | 5x-9=6(x+3) | | 3x+750+12x=200 | | F(x)=e^8x | | (5u^2+u-6)(u^2+3u-2)= | | 2^5x=3/2^7 | | 0,6427=x/7.5 | | 12/9600 | | 0,6427=e/7.5 | | 50-3x=8-9x | | K+8-7k=-22 | | 8+3f=14 | | 3x+6=-43-4x | | (3ax/9^2)^4 | | a=x/b | | (x-y)(x^2-11xy+y^2)= |

Equations solver categories